Baptism in the Holy Spirit a re-examination of the New Testament teaching on the gift of the Spirit in relation to Pentecostalism today - Dunn, James Douglas Grant, 1939- (Philadelphia, PA Westminster, 1970)
Includes bibliographical references and indexes.
Keywords: Baptism in the Holy Spirit -- Biblical teaching